Situation of microbiological contamination in bottled drinking water products and some influencing factors in Hau Giang province in 2020 - Vo Thi Thuy, Loan; Tran Thi Tuyet, Hanh (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Background: Bottled drinking water has become popular for consumption by customers. Bottled drinking water with pathogenic microbiological contamination is a public health concern. This study aimed to describe the current situation of microbiological contamination in bottled drinking water products, food safety conditions and some influencing factors in production facilities in Hau Giang province in 2020. Methods: A cross-sectional study has been conducted in 2020 using quantitative and qualitative methods. The evaluation was carried out at 54 bottled drinking water production facilities, 108 workers/owners and 54 samples collected from facilities for microbiological analysis in the province. In-depth interviews were conducted with local government officials on food safety, two owners of facilities and two workers. Results: It showed that the proportion of microbiological contamination in bottled drinking water accounted for 18.5%, of which P. aeruginosa contamination was 18.5%; and Coliform contamination was 3.7%; No drinking water samples were contaminated with E. coli. 79.6% of facilities met general food safety conditions. There were several factors affecting the proportion of microbiological contamination of bottled drinking water as follows: Bad compliance with food safety in production for the sake of profit by workers, affecting the quality of products such as trash cans without lids; No sterilization treatment before filling; Non-sterilization in filling room. Non-monitoring of UV lights for replacement; No regular cleaning of water pipes, tanks, and discharge valves; Difficulty in state management of food safety for facilities of bottled drinking water production, such as insufficient manpower, lack of equipment and funding for activities. Conclusion: The quality of bottled drinking water in Hau Giang province was not good. The important factors affecting the contaminated bottled drinking water products were identified. We recommend that: management agencies should frequently conduct sudden inspections and supervisions of facilities with no ensured food safety and strictly handle according to regulations. Owners of bottled water facilities should voluntarily comply with food safety. This study is particularly concerned with ensuring food safety conditions in the production of bottled drinking water to prevent products from microbiological contamination.